2021
DOI: 10.1101/2021.08.12.456168
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 spike opening dynamics and energetics reveal the individual roles of glycans and their collective impact

Abstract: The trimeric spike (S) glycoprotein, which protrudes from the SARS-CoV-2 viral envelope, is responsible for binding to human ACE2 receptors. The binding process is initiated when the receptor binding domain (RBD) of at least one protomer switches from a "down" (closed) to an "up" (open) state. Here, we used molecular dynamics simulations and two-dimensional replica exchange umbrella sampling calculations to investigate the transition between the two S-protein conformations with and without glycosylation. We sh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 110 publications
2
5
0
Order By: Relevance
“…before, the closed-to-open transition of the RBD was analysed by performing PCA on the RBD (residues 330-530) and continuous density distributions for PC1 RBD were finally plotted (red and blue dashed lines in Figure5d). In line with other published data(Casalino et al 2020;Pang et al 2021;Rahnama et al 2021), glycosylation seems to affect the extent of the RBD opening. Even more shifted density distributions were in fact registered for both the S:D614G and [S:A222V + S:D614G] mutants…”
supporting
confidence: 93%
See 1 more Smart Citation
“…before, the closed-to-open transition of the RBD was analysed by performing PCA on the RBD (residues 330-530) and continuous density distributions for PC1 RBD were finally plotted (red and blue dashed lines in Figure5d). In line with other published data(Casalino et al 2020;Pang et al 2021;Rahnama et al 2021), glycosylation seems to affect the extent of the RBD opening. Even more shifted density distributions were in fact registered for both the S:D614G and [S:A222V + S:D614G] mutants…”
supporting
confidence: 93%
“…Other map-to-model quality figures, like FSC-Q (Ramírez-Aportela et al 2021), agreed in this respect (data not shown).Molecular dynamics simulations were also carried out to provide complementary and perhaps less discrete structural details about the subject under study. Considering the importance of glycosylation for the spike dynamics(Casalino et al 2020;Pang et al 2021, Rahnama et al 2021, MD trajectories were collected starting from our cryo-EM structures as well as from previously reported structural models with and without glycosylation.Results from PCA relative to the RBD closed-to-open transition pointed out the preference for a more open RBD for the [S:A222V + S:D614G] mutant, with glycosylation additionally enhancing the openness of the open RBD, inagreement with a recent study(Pang et al 2021). Furthermore, dynamic network analysis allowed us to go deeper into the allosteric nature of the possible changes induced by the S:A222V mutation.…”
mentioning
confidence: 99%
“…Since no relevant effects, relative to the observed phenomenon, were produced by the S:A222V mutation on the conformational ensemble of the 3-down closed state (see above), MD simulations were limited to the open 1-up state of the protein for this analysis. Accordingly, 400 ns of MD simulations were run for the S:D614G and [S:A222V + S:D614G] mutants (gly-UDD S:D614G and gly-UDD In line with other published data [17][18][19], glycosylation seems to affect the extent of the RBD opening. Even more shifted density distributions were in fact registered for both the S:D614G and [S:A222V + S:D614G] mutants (respectively centred on 15 and 22 for PC1 RBD ) with respect to the previously simulated systems.…”
Section: Plos Pathogensmentioning
confidence: 68%
“…Molecular dynamics simulations were also carried out to provide complementary and perhaps less discrete structural details about the subject under study. Considering the importance of glycosylation for the spike dynamics [17][18][19], MD trajectories were collected starting from our cryo-EM structures as well as from previously reported structural models with and without glycosylation. Results from PCA relative to the RBD closed-to-open transition pointed out the preference for a more open RBD for the [S:A222V + S:D614G] mutant, with glycosylation additionally enhancing the openness of the open RBD, in agreement with a recent study [18].…”
Section: Plos Pathogensmentioning
confidence: 99%
See 1 more Smart Citation